Mathematical modeling of breakwater-integrated oscillating water column wave energy converter devices under irregular incident waves. (November 2021) - Trivedi, Kshma; Koley, Santanu
Abstract: In the present study, the performance of breakwater-integrated OWC (oscillating water column) wave energy converter devices is analyzed under the action of unidirectional regular and irregular incident waves. Two different types of OWC devices: (i) LIMPET device (sloping-face OWC device) and (ii) quarter-circle-shaped front wall OWC device are considered for the present study. Detailed derivations of the parameters associated with the performance of the OWC devices under the action of irregular waves are provided. To analyze the efficiency of the OWC devices in real sea conditions, the Bretschneider Spectrum is taken as the incident wave spectrum along with nine sea states represent the local wave climate at the OWC plant site Pico, Portugal. The annual-averaged plant efficiencies of the two aforementioned OWC devices are analyzed as a function of chamber length, submergence depth, turbine rotor diameter, and rotational speed of the Wells turbine. It is observed that the annual-averaged plant efficiency can be enhanced significantly with appropriate combinations of chamber length, submergence depth, and turbine characteristics. Highlights: Performance of LIMPET and quarter-circular shaped OWC devices are studied. Local wave climate at site Pico, Portugal is considered as incident wave spectrum. Maximum efficiency for LIMPET occurs for moderate draft and chamber length. Maximum efficiency for circular OWC occurs for moderate draft and chamber radius. Appropriate turbine rotor diameter and rotational speed enhance the OWC efficiency.